2006
DOI: 10.1111/j.1540-8167.2006.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Adjuvant Anterior Left Atrial Ablation During Intracardiac Echocardiography‐Guided Pulmonary Vein Antrum Isolation for Atrial Fibrillation

Abstract: Adjuvant anterior LA ablation does not appear to impact procedural outcome in patients with paroxysmal AF but may offer benefit to patients with persistent/permanent AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(75 citation statements)
references
References 21 publications
3
70
0
2
Order By: Relevance
“…The importance of these sites, as substrates for atrial fibrillation, has been previously demonstrated [18]. As observed in the results of this study the CFE mean map algorithm correlated very well with the human manual operator manual tagging fractionated signal corresponding to PV potentials which was used as the Gold Standard (Table 2).…”
Section: Discussionsupporting
confidence: 67%
“…The importance of these sites, as substrates for atrial fibrillation, has been previously demonstrated [18]. As observed in the results of this study the CFE mean map algorithm correlated very well with the human manual operator manual tagging fractionated signal corresponding to PV potentials which was used as the Gold Standard (Table 2).…”
Section: Discussionsupporting
confidence: 67%
“…We believe that due to the proximity of Bachmann bundle to the antral region of the RSPV [11] in some cases the conduction over this structure is delayed as a result of the ablation, also confirming the ablation of left atrial muscle tissue in the septal region. This has been proven to improve outcome with radiofrequency ablation [12] but for cryothermal ablation the clinical impact of this remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…54 A 200-patient case-control study demonstrated that targeting CFAEs in addition to PVI had no effect on freedom from AF in patients with paroxysmal AF and only marginally improved the success rate of PVI in the subset of patients with persistent or permanent AF (success rate 82 % for PVI and CFAE ablation vs. 72 % for PVI alone, p=0.047). 65 Multiple other studies, however, have found that targeting CFAEs provided no additional freedom from AF over PVI alone even among patients with permanent AF. 57,59,60,63 A recent meta-analysis evaluated the outcomes in 622 patients across seven trials that compared PVI with PVI plus adjunctive CFAE ablation.…”
Section: Limitations Of Targeting Rotors With Ablation For the Treatmmentioning
confidence: 99%
“…Observations that CFAE ablation without PVI results in very high rates of AF recurrence 54,[61][62][63]65 suggest that CFAEs are not drivers of AF. In fact, the vast majority of areas of observed fractionation are actually functional and passive electrophysiological manifestations.…”
Section: Complex Fractionated Electrograms Are Passive Bystanders In Afmentioning
confidence: 99%